PENGENDALIAN MUTU PEMBELAJARAN PADA SEKOLAH MENENGAH KEJURUAN - Endang Herawan Herawan (UIN Imam Bonjol Padang, 2023)
This study aims to verify, describe and interpret data on the quality control of SMKN learning. The research uses a descriptive method with a qualitative approach, with case studies at SMKN 1 and SMKN 3. Data collection is done through interviews, observation, and documentation studies. The results showed that the learning quality control system that was carried out was comprehensive, starting from 1) quality control in preparing learning programs, such as in making learning programs, making teaching preparations, making teaching materials, and evaluation plans, 2) quality control of implementing learning includes implementation of teaching, evaluation of learning outcomes and 3) quality control follow-up. Considering that education in Vocational High Schools is organized in the form of a dual system, namely carried out in schools and in the business and industrial world in the form of practical work, the quality control of learning in Vocational High Schools is not only carried out by school principals, school supervisors through academic supervision activities, it is also carried out by involving external parties, such as the world of business and industry (DUDI) and professional associations, especially in the preparation of learning programs, the formulation of competencies that students must have, in the implementation of learning programs as well as competency assessment or exams, especially those related to productive fields. This is done so that the learning programs and student competencies developed in schools are in accordance with the demands and needs of the world of work.